A Rare Case Report of Epithelioid Haemangioendothelioma of Ovary in Older Age Group - Anisa Barman; Sukla Naskar; Anadi Roy Chowdhury (Journal of Medical Sciences and Health)
Epithelioid haemangioendothelioma is a very rare malignant vascular tumor with metastatic potential. It occurs between 30 – 50 years of age group. Most common sites are lung, liver, and bone. As a site of origin, ovary is the rarest. Few cases are reported till now. We received a specimen of total abdominal hysterectomy and bilateral oophorectomy in a case of 60 years woman, presented with left adnexal mass. Gross and microscopical features showed diagnosis of Epithelioid Haemangioendothelioma. The diagnosis is confirmed by immunohistochemistry study of CD34, Vimentin & Pancytokeratin.